(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to analyze the current status and actual conditions of management and operation of graduate schools within general universities in Korea. In order to analyze the current status and actual condition of graduate schools, 5 areas comprised of 26 items were organized and implemented based on the CIPP evaluation model. The analysis was conducted on the research subjects of 106 graduate schools out of 185 (57.3%). The results of the survey found that Private universities account for approximately 70% of graduate degree programs in Korea, and they are evenly distributed across the country, providing opportunities and accessibility to graduate education. In this process, most of the regulations for major graduate school academic systems are in place. In order to improve the quality of graduate schools in the future, first, it is necessary to review the upward adjustment of the credits required for graduation. Second, there needs to be efforts to manage the quality of theses, and third, there needs to be improvement of the education conditions and support system for graduate schools. Fourth, there is a need to improve the administrative expertise of graduate schools.